Art of the deal : contemporary art in a global financial market - Horowitz, Noah, 1979- (Princeton University Press, 2011)
Noah Horowitz exposes the inner workings of the contemporary art market, explaining how this unique economy came to be, how it works, and where it's headed. He takes a unique look at the globalization of the art world and the changing face of the business, offering the clearest analysis yet of how investors speculate in the market and how emerging art forms such as video and installation have been drawn into the commercial sphere. --Book Jacket.